Analisis Akibat Bolosnya Seorang Siswa di Sekolah - Amini, Amini; Silvia Ningsih, Riza Wati; Manurung, Nabelia Utami; Adelia, Wilda; Alsyah, Siti; Sitepu, Marisa (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
The Guidance and Counseling Instructor's Role in Supervising Private Vocational School Students at School Students' bad behavior known as truancy includes not attending school without permission, missing certain class hours, and returning home after school has begun. The purpose of this study is to ascertain the causes of truancy among students and the consequences of such behavior at school. It is common knowledge that truancy results in learning failure. The descriptive qualitative method was utilized in this study. According to the findings of the research that was carried out, the behavior of truancy is influenced by both internal and external factors like a lack of motivation and interest in learning, juvenile delinquency, and friends who like truants but don't like certain teachers or lessons. They frequently receive calls from counseling teachers as a result of truancy, and they miss lessons, which can result in lower grades or, the most serious outcome, expulsion from school. Keywords: Internal and external factors, truancy behavior